2007
DOI: 10.1111/j.1471-4159.2007.05075.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐specificity tyrosine(Y)‐phosphorylation regulated kinase 1A‐mediated phosphorylation of amyloid precursor protein: evidence for a functional link between Down syndrome and Alzheimer’s disease

Abstract: Caused by the presence of an extra copy of human chromosome 21 (trisomy 21), Down syndrome (DS) is the most common genetic disorder with an incidence of one in 800 live births. DS patients suffer various symptoms, including mental retardation and an early-onset of Alzheimer's disease (AD). The brains of both DS and AD patients show increased amounts of b-amyloid (Ab), which leads to the formation of amyloid plaques, a hallmark of AD pathogenesis (Mann and Esiri 1989). Although the cause of an early-onset AD in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(172 citation statements)
references
References 50 publications
4
158
0
2
Order By: Relevance
“…Mutation of Ser-303 to Ala, but not Ser-280 and Ser-316, increased the promotion of SRp55 in Tau exon 10 inclusion. In addition, it is known that in addition to the consensus sites, Dyrk1A also phosphorylates Ser/Thr within non-consensus site (42)(43)(44)(45). The RS domain of SRp55 has many Ser/Thr resides that probably are phosphorylated by Dyrk1A with low efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of Ser-303 to Ala, but not Ser-280 and Ser-316, increased the promotion of SRp55 in Tau exon 10 inclusion. In addition, it is known that in addition to the consensus sites, Dyrk1A also phosphorylates Ser/Thr within non-consensus site (42)(43)(44)(45). The RS domain of SRp55 has many Ser/Thr resides that probably are phosphorylated by Dyrk1A with low efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism that has been proposed to account for the interplay between DYRK1A and APP is a positive feedback loop (see Cardenas et al, 2012) in which DYRK1A phosphorylates APP at Thr668 (Ryoo et al, 2008) favoring the amyloidogenic cleavage of APP (Judge et al, 2011;Lee et al, 2003), and Aβ42 induces an upregulation of DYRK1A (Kimura et al, 2007). The cooperative effects of these genes could affect tau expression and phosphorylation and result in abnormal expression and hyperphosphorylation, favouring tau aggregation and the destabilization of microtubules.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although the extra copy of APP and its overexpression seems to be the primary cause of amyloidosis in the DS brain, several studies have demonstrated that DYRK1A plays an important role in this process by interacting with APP. DYRK1A phosphorylates APP at Thr668 in vitro in cells of a mouse model that overexpresses the human DYRK1A gene (hBACtgDyrk1A) (Ryoo et al, 2008). This phosphorylation facilitates the excision of APP by β-secretase 1 (Beta-secretase 1, BACE1) and γ-secretase, inducing an accumulation of the neurotoxic peptides Aβ40 and Aβ42 (Wegiel et al, 2011;Vingtdeux et al, 2005;Lee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the transcription factor ETS2 is thought to transactivate the APP promoter, leading to overexpression 123 . The chromosome 21-encoded proteins small ubiquitin-related modifier 3 (SUMO3) and dualspecificity tyrosinephosphorylation-regulated kinase 1A (DYRK1A) modify APP posttranslationally, which may alter Aβ generation [124][125][126] . Additionally, the chromosome 21 microRNA miR-155 has been suggested to modulate γ-secretase activity and hence the processing of APP, through its effect on the expression of sorting nexin 27 (REF.…”
Section: Interaction Of Other Chromosome 21 Genes With Appmentioning
confidence: 99%